New Testament commentaries for English readers ; vols. 2 and 3 - Ellicott, Charles John, 1819-1905 (London, UK Cassell, 1901)
Contents : v. 2 : Acts, Romans, I & II Corinthians, Galatians; v. 3 : Ephesians,Philippians, Colossians, Thessalonians, Timithy, Titus, Philemon, Hebrews, James, 1st Peter, 2nd Peter, Epistles of John, Jude, Revelation.
Keywords: Bible. N.T. -- commentaries